2013
DOI: 10.4081/itjm.2010.173
|View full text |Cite
|
Sign up to set email alerts
|

Severe exacerbations of chronic obstructive pulmonary disease: management with noninvasive ventilation on a general medicine ward

Abstract: Introduction: Recent evidence suggests that, with a well-trained staff, severe exacerbations of chronic obstructive pulmonary disease (COPD) with moderate respiratory acidosis (pH > 7.3) can be successfully treated with noninvasive mechanical ventilation (NIMV) on a general respiratory care ward. We conducted an open prospective study to evaluate the efficacy of this approach on a general medicine ward. Material and methods: This study population consisted in 27 patients admitted to a general medicine ward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…However, the pH level has been reported to be a crucial factor in determining the NIV success rate. 4,5 Although the confidence of healthcare providers with NIV has progressively improved and although NIV has been applied with success also outside the critical care environment, 6,7 to date NIV is not recommended outside ICU in patients with severe hypercapnic ARF and a pH < 7.30. 8 In particular, it was shown that NIV treatment failed in approximately 50-60% of COPD-exacerbated subjects with a baseline pH < 7.25.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pH level has been reported to be a crucial factor in determining the NIV success rate. 4,5 Although the confidence of healthcare providers with NIV has progressively improved and although NIV has been applied with success also outside the critical care environment, 6,7 to date NIV is not recommended outside ICU in patients with severe hypercapnic ARF and a pH < 7.30. 8 In particular, it was shown that NIV treatment failed in approximately 50-60% of COPD-exacerbated subjects with a baseline pH < 7.25.…”
Section: Introductionmentioning
confidence: 99%
“…Nello schema sopra riportato non viene considerata la possibile alternativa delle cosiddette ''Unità di Cure Intermedie'' (''High Dependency Units''), ovvero di aree ad alta intensità assistenziale (''high care''), implementabili anche nei reparti di Medicina Interna [34], particolarmente adatte per quei pazienti che hanno un basso rischio attuale ma sono suscettibili di complicanze maggiori e richiedono un monitoraggio di routine [35].…”
Section: Il Percorso Clinico-assistenziale Del Paziente Ricoveratounclassified